Morphological and molecular characterization of mud lobster and determination of its antioxidant and anti-inflammatory activities. - Zakaria, Nur Nadiah (2020)
Mud lobsters (Thalassina spp.) are locally referred to as ‘udang ketak’ or ‘ketam busut’ are considered as an important organism in the mangrove ecosystem for its burrowing activities and the role of its mounds or burrows as home to other animals. In Malaysia and Thailand, mud lobsters are eaten by locals as treatment for asthma. It is traditionally believed that they are effective in reducing the number of asthma attacks and severity of asthma symptoms. However, the therapeutic potential of mud lobster remains unclear and has not been fully elucidated or reported in scientific study. Present study builds on that knowledge to determine the species of mud lobster and test the potential of mud lobster as natural antioxidant and anti-inflammatory. The objectives of this study are to identify species of mud lobster through analysis of morphological traits and molecular gene markers (PEPCK and CO1), to analyse sexual dimorphism and length-weight relationship of mud lobster and to investigate antioxidant and anti-inflammatory potential of mud lobster extracts and determine the bioactive compounds involved. All mud lobster samples (n=70) collected from four distinct regions in Sarawak (Kuala Tatau, Kuala Balingian, Sarikei and Lingga) were identified as Thalassina anomala through morphological characteristics and molecular gene markers (PEPCK and CO1). Maximum likelihood tree analysis of CO1 gene sequences showed that T. anomala from all populations were closely related with each other with 100% bootstrap supporting evidence. For morphometric variations between sex, specimens with damaged or missing cheliped were not included in analysis. Sexual dimorphism of T. anomala can be observed where males are significantly longer for carapace and left chelae propodus compared to females (p<0.05). Meanwhile, the abdominal width was significantly larger in females. The length-weight relationship of T. anomala showed that males had isometric growth rate for carapace length-weight (CL/W), total length-weight (TL/W) and abdominal length-weight (ABL/W) relationships. However, females had negative allometric growth in CL/W and ABL/W relationship and isometric growth in TL/W relationship. Antioxidant potential of T. anomala extracts (methanol, chloroform and hexane) were analysed through DPPH, ABTS and FRAP assays. The chloroform extract was identified to have higher antioxidant activity except in DPPH assay in which the methanol extract exhibited higher antioxidant activity. The results suggested that all T. anomala extracts have antioxidant potential and this finding was confirmed by presence of radical scavenging activity in antioxidant assays. For anti-inflammatory investigations, the hexane extract of T. anomala showed anti-inflammatory activity by significantly inhibit the LPS-induced production of nitric oxide, prostaglandin PGE2, interleukin- (IL-) 6, IL-1β and tumor necrosis factor-alpha (TNF-α) in a concentrationdependent manner. GC-MS analysis of the hexane extract revealed the presence of 19 putative compounds with anti-inflammatory activities. The peaks of putative compounds were identified by comparing the retention times with data from NIST and WILEY libraries. Highest peaks detected are cholesterol (C27 H46 O) and butyric acid (C4 H8 O2). Overall, results from this study showed evolutionary relationship, sexual dimorphism and growth pattern of T. anomala from Kuala Tatau, Kuala Balingian, Sarikei and Lingga, Sarawak. This present study also suggested that T. anomala extracts have antioxidant and anti-inflammatory potential.